The Mechanical and Electrical Properties of the Ternary Bi-Ga-Sb System - Minić, Duško; Premović, Milena; Čikara, Dejan; Mitrovica, Kosovska; Manasijević, Dragan; Živković, Dragana (Materialprüfung, 2014)
The ternary Bi-Ga-Sb system is a potential soldering material. The gallium-based alloy systems are the subject of numerous investigations due to the constant interest of the semiconductor industry. For a more complete characterization of the ternary Bi-Ga-Sb system, alloys from the three vertical sections were investigated using microstructural analysis as well as electrical conductivity and Brinell hardness measurements. The microstructures of the alloys were investigated by light microscopy and scanning electronic microscopy equipped with energy dispersive spectrometry. Isolines of electrical conductivity and hardness for the entire Bi-Ga-Sb system were calculated using regression models. In addition, a thermodynamic assessment of the system has been carried out by calculation of the isothermal section at 100 °C and by description using the CALPHAD method. Experimental and analytical results were found to be in good agreement.